Antiviral Efficacy of Disinfectant Solution MRI-1 - Skinner, G.R.B.; Billstrom, M.; Randall, S.; Buchan, A.; Davies, J.; Ahmad, A. (Intervirology, 1998)
Disinfectant MRI-1 was prepared by dissolution of non-ionic and ionic detergent in ethanol. The disinfectant inactivated extracellular and intracellular enveloped and non-enveloped viruses including herpes viruses, influenza A and human immunodeficiency disease virus in suspension or on surfaces by pre-exposure or post-exposure to the disinfectant; in addition, cells were disabled as potential hosts for viral infection using concentrations of MRI-1 which were 50-fold less than the operative concentration for disinfection. There was no evidence of in vitro mutagenicity using Salmonella typhimurium or sensitization or other adverse effect in a guinea pig model or in human subjects.